Consumer Information Tracking in E-Commerce from APersonal Data Protection Perspective: A Comparative Analysis of Vietnamese and Japanese Legal Frameworks - Thuy, Phan Thi Thanh (VNU Journal of Science: Legal Studies; Vol 42 No 1, 2026)
Amid the rapid growth of the digital economy, e-commerce businesses are increasingly tracking consumer information, essentially by processing behavioural data, to enable personalised marketing and improve business performance. This trend raises legal challenges for the protection of personal data in general and consumer information in particular. Although Vietnamese law has established a basic legal framework for personal data protection and consumer protection, it still lacks direct and specific rules to regulate online consumer-tracking practices. This article examines the current legal landscape governing the protection of consumer information in Vietnamese e-commerce, compares it with the legal framework in Japan, and identifies regulatory gaps as well as the legal mechanisms that should be added to ensure that consumers can conduct transactions in a secure and privacy-preserving manner.